ОСОБЕНОСТИ ЮРИДИЧЕСКОЙ ОТВЕТСТВЕННОСТИ ЗА СОВЕРШЕНИЕ БУЛЛИНГА В УКРАИНЕ: ПРАКТИЧЕСКИЙ АСПЕКТ - Toronchuk, Ivan; Krainii, Pavlo (Centrul Editorial-Poligrafic al USM, 2021)
In the modern world, where the role and influence of various social networks are permanently increasing, there take place numerous changes in the structure of both society on the whole, and the interaction of each of its participants in particular. Consequently, there arises urgent necessity to revise the attitude towards the phenomena that were not so essential before. Undoubtedly, the issue of bullying is extremely important and relevant for the Ukrainian society. The legislation of our country has always relied on the understanding of bullying in the way it was formulated and postulated in the Western countries. However, recently, there have been introduced certain important changes into the regulatory-legal acts that suggest administrative liability for bullying. Besides, there has been given a definition of the concept of bullying that took into account its basic features and peculiarities. On the other hand (as it is shown by the practice of law enforcement of the provisions on prosecution for bullying), the legislator, intentionally or accidentally, limited himself to the possibility of prosecuting for actions that are qualified as bullying, only within the framework of the Code of Administrative Offenses of Ukraine (hereinafter, referred to as the CAOU). What is more, this phenomenon is fixed only in relation to the educational process, emphasizing such special subjects as teachers and students. There also exists judicial practice regarding the application of CAOU for bullying. However, due to the fact that very often minors succumb to various psychological pressure and actions that lead to severe psychological consequences (trauma, illness), administrative responsibility for such offenses will not be enough. The purpose of this article is to substantiate the amendments to the Criminal Code of Ukraine, to determine a new essence of a criminal offense for committing bullying, as well as to strengthen liability and punishment for it.
Keywords: bullying; legal liability; criminal offense